Risk Factor Analysis for Late-onset Neonatal Hyperbilirubinemia in Taiwanese Infants - Mi-Shu Huang; Ming-Chih Lin; Hsiu-Hsi Chen; Kuo-Liong Chien; Chao-Huei Chen (Pediatrics and Neonatology)
Neonatal hyperbilirubinemia is a recognized health risk for newborns. It can cause kernicterus and hearing impairment. Certain groups of infants who do not have significant jaundice during the first few days of life develop hyperbilirubinemia later. Because early discharge is a worldwide trend, prompt identification of this group of infants is of paramount importance in preventing complications. Methods: The data used were derived from a medical center. A total of 523 term or near-term infants were enrolled in this study. All infants were scheduled for follow-up visits. In this study, late-onset neonatal hyperbilirubinemia was defined as a total bilirubin level greater than 15 mg/dL, or receiving phototherapy at 5-7 days. Newborns that had clinically significant jaundice within 96 hours of life were excluded from analysis. Univariate and multivariate logistic regressions were applied for statistical analysis. Results: One hundred and eighty infants were included for data analysis. Thirty-nine (21.7%) had late onset hyperbilirubinemia. Exclusive breast-feeding and less body weight loss during the 1st day of life were both significant risk factors for late onset hyperbilirubinemia. However, early discharge was not associated with late-onset hyperbilirubinemia. Conclusion: Thirty-nine (21.7%) infants develop late hyperbilirubinemia at the age of one week. Exclusive breast-feeding and less body weight loss were significant risk factors. Follow-up visits are recommended for all infants, especially for those who have these risk factors.